KORBAN TINDAK PIDANA PERKOSAAN (Studi Putusan Nomor 358/Pid.Sus/2016/PN.Mdn) - Fakhrul Raji (Universitas Islam Sumatera Utara, 2018)
Attention and protection of the victims’ interests of the crime of rape either through the criminal justice process or through certain social care facilities is an absolute part that needs to be considered in criminal law policies and social policies, both by the executive, legislative and judicial institutions as well as by social institutions which exists. This research uses a descriptive method through a normative approach (legal research), namely an approach to problems which carried out by examining various legal aspects in terms of applicable regulations. In the context of protection for victims of crime, there are preventive and repressive measures taken, both by the community and the government (through law enforcement officers), such as providing protection/supervision from various threats that can endanger the lives of victims, providing adequate medical and legal assistance. The process of examination and fair trial of perpetrators of crimes is basically a manifestation of the protection of human rights as well as a balancing instrument. This is where the philosophical basis behind the importance of crime victims (their families) getting protection. Keywords: Legal Protection, Victims, Rape